ROLE OF NATURAL LANGUAGE IN SOCIO-CULTURAL SPACE REPRESENTATION INFORMATION AGE - Антіпова, О. П. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2015)
In the article the specificity of the representation of cultural phenomena of the information age by means of natural language.